Performance of asphalt mixture incorporated with tin ore tailing - Putra Jaya, Ramadhansyah; Yuan, L.; K. A., Masri; Intan Suhana, Mohd Razelan; A. H., Norhidayah; M. N., Mohd Warid (IOP Publishing Ltd, 2021)
Tin Ore tailings (TOT) are waste generated from tin mining activities, which not only occupy lots of land, but also result in severe pollution to the surroundings. Many studies by researchers exploring better ways to increase the usage of industrial by-products in order to ease disposal problems preserve natural sources and save the environment. In this study, 1%, 3% and 5% of TOT are incorporated with ACW14 mixture in accordance to JKR 2008. 5% optimum bitumen is used for all samples. Marshall Mix design test is conducted to determine the volumetric properties, stability and flow. Moisture susceptibility test conducted to determine the indirect tensile strength in dry and wet samples. Generally, the stability values increases with the percentage of TOT increased.